WINDOW DESIGN BY LEILA MENSHARY FOR HERMÈS - Лю, П. (Art and Design, 2023)
The purpose of the research is to analyze the background and history of the formation of the author’s style of Leyla Menshari, the leading Hermès decorator artist in the design of the brand’s showcases, to explore the themes, methods and means of creating showcase installations that distinguish the brand from many others. Methodology is determined by a comprehensive study of the window display of a certain brand and includes: methods of analysis, synthesis, image-stylistic and structural-system analysis of exclusive author’s samples, historical and comparative methods. Results. The degree of study of the topic in the scientific and professional literature of leading domestic and foreign authors is determined; analyzed the sources that outline the historical development of window displays of the French fashion house Hermès during the second half of the 20th and the beginning of the 21st centuries. The main approaches to the design of the brand’s showcases that have developed historically are indicated, the key themes of the expositions, typical and innovative approaches in their design, differences and peculiarities are outlined. The characteristic features of L. Menshari’s individual creativity and its significance for the art of window displays in the world are studied. The scientific novelty of the study consists in a comprehensive consideration of the "art of shop windows", the works of which nowadays attract more and more attention and are of great importance in the development of modern visual culture, covering the meaningful and material aspects of the design of shop windows as artifacts and works of art. The practical significance. The materials of the article can be used in the educational process as unique examples of costume design representations in the training of fashion design specialists, as well as in the training of window dressers as specialized specialists in decorative and applied art and exhibition design, when writing scientific papers.